PERSPEKTIF BIBLIOMETRIK TERHADAP INTEGRASI METAVERSE DALAM PENDIDIKAN: TREN PUBLIKASI, PENULIS, DAN ARAH PENELITIAN TERKINI - Muhammad Fadli; Dian Sri Purwanti; Windia Hanifah; Valdi Mughni Budiman; Rifka Simbolon; Riyan Maruly; Amarudin (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The Metaverse has emerged as a promising digital technology in education due to its ability to create immersive, interactive, and collaborative learning environments. This study aims to analyze the development of research on the integration of the Metaverse in education through a bibliometric approach. The research data were collected from the Dimensions database using the keywords “Metaverse” and “Education,” resulting in a total of 636 publications published between 2015 and 2025. Bibliometric analysis was conducted and visualized using VOSviewer software to identify publication trends, productive authors, leading contributing countries, and emerging research themes. The findings reveal a significant increase in the number of publications since 2021, with the highest publication output recorded in 2024. China, South Korea, and the United States were identified as the leading contributors to the field, while Hwang G.J. was recognized as one of the most prolific authors. Keyword network analysis indicates that the dominant research themes focus on the Metaverse, Virtual Reality, Augmented Reality, learning, and immersive learning experiences. Furthermore, emerging topics such as digital twins, artificial intelligence, and technology acceptance have begun to gain attention as potential directions for future research. These findings suggest that Metaverse research in education is developing in a multidisciplinary manner and holds significant potential to support the transformation of digital learning in the future.